DETERMINAN FAKTOR KEJADIAN CA MAMMAE PADA REMAJA-DEWASA AWAL DI RSUD KOTA BOGOR - Andriati, Riris; Rahayu, Safitri; Sarah, Fitri; Fadhilah, Humaira; Iskandar, Arik (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2026)
ABSTRAKCa Mammae is the most prevalent cancer among early adult women aged 15–39 years, accounting for 5.6% of all invasive breast cancer cases in younger women compared to older age groups (Rebecca H. Johnson, MD, 2021). In 2023, the Bogor City Health Office reported breast cancer as the leading cancer type, with 597 recorded cases. This study aimed to identify determinants of Ca Mammae incidence among adolescents and early adults at Bogor City Hospital. A quantitative study with a descriptive cross-sectional design was conducted. The population consisted of 30 adolescents–early adults diagnosed with Ca Mammae, with total sampling applied. Data were analyzed using Chi-Square tests and multivariate binary logistic regression. Statistical significance was set at p 0.05. The results showed significant associations between Ca Mammae incidence and age at menarche (p = 0.037), family history (p = 0.011), stress (p = 0.042), and consumption of ready-to-eat food (p = 0.033). No significant association was found between obesity and Ca Mammae incidence (p = 0.261). Multivariate analysis identified consumption of ready-to-eat food as the most dominant determinant factor (p = 0.018). In conclusion, dietary patterns, particularly the consumption of ready-to-eat food, represent the strongest contributing factor to Ca Mammae incidence among adolescents and early adults at Bogor City Hospital. The findings are expected to serve as a scientific reference and educational resource for STIKes Widya Dharma Husada Tangerang in strengthening academic materials related to determinants of Ca Mammae incidence in young populations                                                 ABSTRACTCa Mammae merupakan kanker yang paling prevalen pada perempuan dewasa awal berusia 15–39 tahun, dengan proporsi sebesar 5,6% dari seluruh kasus kanker payudara invasif pada kelompok usia muda dibandingkan kelompok usia yang lebih tua. Pada tahun 2023, Dinas Kesehatan Kota Bogor melaporkan kanker payudara sebagai jenis kanker tertinggi, dengan jumlah kasus sebanyak 597. Penelitian ini bertujuan untuk mengidentifikasi determinan kejadian Ca Mammae pada remaja dan dewasa awal di Rumah Sakit Kota Bogor.Penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif menggunakan pendekatan potong lintang (cross-sectional). Populasi penelitian terdiri dari 30 remaja dan dewasa awal yang didiagnosis Ca Mammae, dengan teknik pengambilan sampel total sampling. Analisis data dilakukan menggunakan uji Chi-Square dan regresi logistik biner multivariat, dengan tingkat signifikansi statistik ditetapkan pada p 0,05.